(untitled) (Brazilian Journal of Health Research, 2025)
The formulation of a well-structured research question is a crucial step in the development of a scientific study. It defines the direction of the investigation and influences its methodological design, data analysis, and the relevance of results. This editorial explores the essential criteria for constructing robust research questions, emphasizing the use of structured frameworks such as PICOT (Population, Intervention, Comparator, Outcome, Time) and FINER (Feasible, Interesting, Novel, Ethical, Relevant). Furthermore, it highlights ten key strategies that guide researchers in refining their questions, including literature review, stakeholder perspectives, and methodological feasibility. The text also discusses common challenges faced during this process, especially by early-career researchers, and presents best practices to overcome them. A strong research question enhances study quality, replicability, and scientific contribution. Therefore, investing in its careful formulation is a strategic step toward producing impactful and reliable scientific knowledge.